Media Pembelajaran Kartu Domino dalam Meningkatkan Kosakata Bahasa Jerman - Dian Luviana; Wahyu Kurniati Asri; Syarifah Fatimah Al Ilmul (Phonologie : Journal of Language and Literature, 2022)
Abstract. The purpose of this study was to determine the mastery of German vocabulary in class X IPA 1 SMA Negeri 4 Selayar using domino card learning media. The type of research used is Classroom Action Research which consists of two cycles, namely cycle I and cycle II. The subjects in this study were students of class X IPA 1 SMA Negeri 4 Selayar, totaling 30 people. Data analysis techniques in this study consisted of qualitative and quantitative. Qualitative data was obtained through observation while quantitative data was obtained through vocabulary improvement tests in cycle I and cycle II. The results of the German vocabulary mastery test showed that the average score in the first cycle was 73.20 and the second cycle was 86.29. The results of this study indicate that the domino card media can increase the German vocabulary of class X students of SMA Negeri 4 Selayar.Keyword: Enhancement, Vocabulary, Dominoes Card Media